-5(m+8)=-2(m+8)

Simple and best practice solution for -5(m+8)=-2(m+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(m+8)=-2(m+8) equation:


Simplifying
-5(m + 8) = -2(m + 8)

Reorder the terms:
-5(8 + m) = -2(m + 8)
(8 * -5 + m * -5) = -2(m + 8)
(-40 + -5m) = -2(m + 8)

Reorder the terms:
-40 + -5m = -2(8 + m)
-40 + -5m = (8 * -2 + m * -2)
-40 + -5m = (-16 + -2m)

Solving
-40 + -5m = -16 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-40 + -5m + 2m = -16 + -2m + 2m

Combine like terms: -5m + 2m = -3m
-40 + -3m = -16 + -2m + 2m

Combine like terms: -2m + 2m = 0
-40 + -3m = -16 + 0
-40 + -3m = -16

Add '40' to each side of the equation.
-40 + 40 + -3m = -16 + 40

Combine like terms: -40 + 40 = 0
0 + -3m = -16 + 40
-3m = -16 + 40

Combine like terms: -16 + 40 = 24
-3m = 24

Divide each side by '-3'.
m = -8

Simplifying
m = -8

See similar equations:

| -4=x-3/2 | | 3-2y-1=4y-7 | | 4x-18=9x+6 | | -9(4-x)-(1+7x)=-25 | | X+3y+27=0 | | 3/4×4= | | 9+2x+14=x+17 | | 3+c=13 | | 4/5÷8/9= | | 3a-4=-9 | | 4/5x-4=12 | | x^2y-3xy^2= | | -8y+24=-5(y-6) | | 3(2-b)=36 | | 5-x/6=1 | | 12-2x/48=3x-6/72 | | 120=-20x | | 2t+6=6t-10 | | 7x+8-4x=10 | | x^3+3x^2-25x=75 | | .08-.12(x-4)=.03(x-5) | | x-5+x+x+2=45 | | 7(2+2n)-7=-91 | | 7-5y=102 | | 3(-3)-y=7 | | 3/(2x-9)=8-3x | | 8-(w+7)=.5 | | (4/5)*5 | | 8(y-1)=6(2y-6) | | -3(v-4)=12-3v | | 2v+17=23 | | 4x-5=5x+21 |

Equations solver categories